Studies on a paradox in the work of the upper limbs in isometric stretching - Ranchev, S.; Ivanov, I.M.; Iotov, I.; Stoytchev, S. (Journal of Applied Sports Sciences, 2020)
Stretching is a common activity used by athletes, elderly, rehabilitation patients, people in-volved in fi tness programs and many others. In isometric stretching an elongation in the linear dimensions of the kinematic chain of the upper limbs is observed. The aim of this study is to show the importance of intraarticular processes as response of isometric stretching force, as well as to mark the basic factors which define the joint answer to stretching, describing experimental data, relative to these factors. The present work has a programmatic character in terms of the directions in which the answer to the laid aims should be sought. The main focus is on the biomechanical processes in the joints involved in the obtained kinematic chain extension.